Energy, exergy, and economic (3E) of a single slope solar still by integrating hollow circular fins and soybean wax as a thermal energy storage system - Irfan Santosa; Muhamad Dwi Septiyanto; Solikin Andriyanto; Eko Prasetya Budiana; Syamsul Hadi (Mechanical Engineering for Society and Industry, 2026)
Energy, exergy, and economic value are examined for the efficiency and sustainability of a unique design for a single-slope solar still that utilizes hollow cylindrical fins and soybean wax as a phase change material (PCM). The three cases outlined, among others: case 1, a conventional single slope solar still (CS4); case 2, with hollow cylindrical fins (HCFS4), and case 3 with hollow cylindrical fins and soybean wax as PCM (HCFSWS4). Performance experimental evaluations of the three cases under the same meteorological conditions ensure a fair comparison of their performances and are carried out for 5 days of testing. The experimental results show that the distillate water yield over five days is 0.986 L/m2/day, 1.243 L/m2/day, and 1.364 L/m2/day for cases 1, 2, and 3, respectively. Also, the maximum energy efficiencies of cases 1, 2, and 3 are 48.9%, 66.1%, and 77.6%, respectively. It is observed that the average exergy efficiency in cases 1,2, and 3 is 33%, 40%, and 42%, respectively. Furthermore, economic analysis findings revealed that the costs per liter per square meter for cases 1, 2, and 3 are 0.06$/L/m2, 0.05$/L/m2, and 0.05$/L/m2, respectively.